Moving beyond international norm emergence –diffusion, contestation and adaptation of an international norm: the case of the responsibility to protect (R2P) - Zähringer, Natalie (My University, 2020)
This study builds on the work done by leading constructivist theorists around norm evolution, from emergence, diffusion to contestation. It outlines a conceptual framework to guide research on norms and proposes a cyclical model in an effort to map the evolutionary process. The Responsibility to Protect (R2P) was chosen as the case study. The research aimed to identify the different meanings-in-use around the R2P norm, the causes of these divergences, as well as the consequences of various types of norm contestation on the norm evolution process. The levels of analysis focused on the global, regional and state level by conducting within-in case comparisons that include the United Nations, the African Union and South Africa. The focus was on contextualising the evolutionary process of norms, emphasising the relevance of the historical, institutional and cultural context in contrast to pursuing a solely rationalist approach. This study was pursued through a series of published articles across local and international journals.
A dissertation submitted to the Faculty of Humanities, University of Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree: Doctorate of Philosophy (International Relations)